2014
DOI: 10.1016/j.ijdevneu.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of visual and auditory evoked potentials in fragile X syndrome

Abstract: The AEP/VEP profile suggests disruptions in sensory processing specific to FXS that exceed immaturity of physiological activity. In addition, the auditory modality seems to be more affected than the visual modality. Results are discussed in light of possible underlying neuronal mechanisms, including deficits in synaptic pruning and neuronal inhibition that might account for a hyperreactive nervous system in FXS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 37 publications
6
59
0
Order By: Relevance
“…FXS patients showed significantly increased phase-locking in alpha frequencies during the stimulus onset time period and decreased theta frequency phase-locking and increased alpha frequency phase-locking after stimulus offset (Fig. 2c), consistent with increased ERP amplitudes found in previous work [40, 41]. As expected, FXS showed decreased gamma phase-locking to the chirp stimulus from 30–58 Hz and decreased gamma phase-locking to the chirp harmonic from 47–58 Hz (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…FXS patients showed significantly increased phase-locking in alpha frequencies during the stimulus onset time period and decreased theta frequency phase-locking and increased alpha frequency phase-locking after stimulus offset (Fig. 2c), consistent with increased ERP amplitudes found in previous work [40, 41]. As expected, FXS showed decreased gamma phase-locking to the chirp stimulus from 30–58 Hz and decreased gamma phase-locking to the chirp harmonic from 47–58 Hz (Fig.…”
Section: Resultssupporting
confidence: 91%
“…The increased alpha phase-locking is consistent with previous findings of increased amplitude early ERP components in response to brief auditory stimuli in FXS [26, 40, 41]. Decreased theta frequency phase-locking simultaneous to stimulus offset is a novel finding in FXS.…”
Section: Discussionsupporting
confidence: 90%
“…Two studies of auditory evoked potentials (AEPs) and VEPs found that the amplitudes in both modalities were increased in FXS compared to both chronological (VEP only) and developmental (both VEP and AEP) control groups (Knoth et al, 2014). This profile suggests disruptions in sensory processing in FXS and supports the notion of a hyper-reactive nervous system.…”
Section: Local Circuits and Networkmentioning
confidence: 99%
“…Individuals with mutations of NLGN4X-coding genes, expressed in inhibitory and excitatory synapses(84), were more likely to exhibit ASD and showed abnormal ERP to auditory deviance detection. In Fragile X syndrome, both auditory and visual ERP amplitudes were increased(85). This finding suggests hyper-excitable neural responses, most prominent in audition, in a genetic syndrome with known glutamate disruption and causing ASD.…”
Section: Electrophysiology and Magnetoencephalographymentioning
confidence: 99%